Tubridge flow diverter alone vs. Tubridge flow diverter and coils for the treatment of intracranial aneurysms: A propensity score matching analysis - Shi, Min; Feng, Yu; Zhang, Cheng-Da; Tang, Qing-Wen; Li, Ze-Jin; Zhao, Wen-Yuan; Zhang, Ting-Bao (Frontiers in Neurology, 2022)
Background The study was designed to assess the clinical performance of a tubridge flow diverter (TFD) in the treatment of intracranial aneurysms and to compare the efficacy and safety between intracranial aneurysms treated with TFD alone and TFD combined with coiling. Methods In this retrospective study, patients treated with the TFD alone or TFD combined with coiling between June 2018 to November 2022 were included. The patient demographics, the characteristics of the aneurysm, and the treatment outcomes between the two groups were compared. Propensity score matching was performed to match the variables with a significant difference between groups. Results In the current study, data from 93 consecutive patients including 104 aneurysms treated with TFD were analyzed. In total, 43 patients with 49 aneurysms were treated with TFD alone, and 50 patients with 55 aneurysms were treated with TFD combined with coiling. Aneurysms in the TFD combined with the coiling group were larger (12.9 ± 8.6 vs. 8.7 ± 8.8 mm, P = 0.016) and more likely to be saccular (92.7% vs. 75.5%, P = 0.027) than in the TFD alone group. No significant difference was observed between the two groups in terms of perioperative complication rate. During the follow-up period, the complete occlusion rate in the TFD combined with the coiling group was higher (80.0% vs. 43.8%, P = 0.001) than in the TFD alone group. These results were further confirmed using a propensity score matching analysis. Conclusion TFD combined with coiling can be a safe and effective alternative option for the treatment of complex aneurysms. Given the potential risks of these therapeutic modalities, thus very careful consideration is required on an individual patient basis.